A CNN-based 3D patch registration approach for integrating sequential models in support of progress monitoring. (August 2019) - Lei, Lei; Zhou, Ying; Luo, Hanbin; Love, Peter E.D.
Abstract: Significant advancements in three-dimensional (3D) imaging technologies have enabled the ability to effectively monitor and manage the progress of works in construction. Traditionally, 3D point clouds have been used in conjunction with building information models to visualize the progress of works. The discrepancies between 'as-planned' and 'actual' models are unable to be automatically identified using the existing approaches due the absence of an effective registration algorithm. To ensure the registration accuracy of multi-scanned point clouds, an automated method based on a data-driven Convolutional Neural Network (CNN) deep learning algorithm is proposed. In this instance, 3D Point cloud patches are aligned with spatial datasets that are scanned from different locations using range cameras. The registration results are used to automatically detect spatial changes when compared with different point clouds. The quantified changes are utilized to determine the percentage of work that has been completed at fixed intervals. The developed registration approach is tested and validated using a series of experiments. It is demonstrated that discrepancies between 'as-planned' and 'actual' models can be identified with a higher level of accuracy, which can enable the baseline for monitoring construction to be undertaken in real-time.